A Case Study of the Psychological Impact of Early Marriage on Women - Selfia Fitriani; Tarisatul Ilmi; Kailla Yuka Febrianti; Yona Viola Adelia (The Future of Education Journal, 2026)
Early marriage resulting from premarital pregnancy often places young women in a psychologically vulnerable position from the outset, particularly by fostering maladaptive patterns of thinking. Such conditions substantially influence how individuals make important decisions in their intimate relationships, including the decision to seek divorce. This study aims to analyze the cognitive dynamics underlying divorce decision-making among young women who experienced marital infidelity following early marriage. The study employed a qualitative case study design using a phenomenological approach. Data were collected through semi-structured in-depth interviews with three female participants: N (19 years old), R (21 years old), and A (20 years old), all of whom were single mothers at the time of the study. Data were analyzed using Aaron Beck's Cognitive Behavioral Therapy (CBT) framework, encompassing automatic thoughts, core beliefs and maladaptive schemas, cognitive distortions, behavioral patterns, and coping strategies. The findings revealed that all three participants shared three dominant maladaptive schemas: feelings of worthlessness, dependence on social approval, and self-punishment, all of which originated from the stigma associated with premarital pregnancy. These schemas were reinforced by cognitive distortions, including catastrophizing, personalization, negative labeling, and should statements, which collectively contributed to their prolonged persistence in unhealthy marriages. Divorce was ultimately pursued only after repeated incidents of marital infidelity provided sufficient external evidence to challenge these deeply rooted cognitive barriers. These findings suggest that CBT-based psychological interventions are essential for young women with similar backgrounds to help them identify and modify maladaptive core beliefs at an earlier stage, thereby promoting healthier relationship decisions.